Analisis Kasus Pembunuhan Istri oleh Suami di Ganet - Aliana .; Ryani .; Tiara .; Marisa Elsera (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
Domestic homicide has become a serious social problem because violence within the household often ends in the loss of life. This study examines the murder case committed by a husband against his wife in Ganet, Tanjungpinang, which attracted public attention due to the element of mutilation carried out by the perpetrator. The purpose of this study is to analyze the factors causing domestic homicide and to examine the case through Travis Hirschi’s social control theory. This study uses a descriptive qualitative method with secondary data sources obtained from online news reports, journal articles, and relevant literature related to the case. The analysis technique was carried out through literature review and interpretation of social phenomena related to domestic violence and criminal behavior. The results show that the murder was not a spontaneous act, but rather the accumulation of prolonged domestic conflict, psychological pressure, weak emotional attachment, and the failure of social reintegration after imprisonment. The perpetrator’s status as a recidivist also contributed to the emergence of extreme violence. Based on social control theory, the weakening of attachment, commitment, involvement, and belief encouraged deviant behavior. In addition, the incident caused social fear, reduced public trust, and created stigma toward the victim’s and perpetrator’s families. Therefore, strengthening social control, family communication, and community participation are important efforts to prevent domestic violence